KOMPARASI HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI MAKE A MATCH DANCARD SORT MATA PELAJARAN AKIDAH AKHLAK KELAS X MADRASAH ALIYAH - Faridhotul Zahro’; Ju’Subaidi Ju’Subaidi (MA'ALIM: Jurnal Pendidikan Islam, 2020)
The purpose of this study was to find out the difference between student learning outcomes using the make a match strategy and Card Sort strategy in the subjects of AkidahAkhlaq on X grade students in Aliyah Madrasah. This research is a quantitative research with comparative analysis. The subjects of this study were26 X grade studentsof MA M'arifBalong. Data collection used test instruments, while data analysis techniques used the "t" test analysis formula. The results of this study indicate that students who use the make a match strategy were 69.23% in the good category, the sufficient category is 0%, and the less category is 30.77%. While the percentage of learning outcomes of students who use the card sort strategy were 46.15% in the good category, the sufficient category is 0%, and the less category is 53.85%. This shows a significant difference between student learning outcomes using the strategy to make a match and card sort strategy. It is proven by the test "t" obtained t0 = 50.55 at a significant level of 1% tt = 2.80 and at a significant level of 5% tt = 2.06 so that t_0>t_t means Ha is accepted. It means a strategy of making a match is suitable for AkidahAkhlaq because it can improve student learning outcomes while the card sort strategy is not suitable for use in AkidahAkhlaq.Keywords:Learning outcome, make a match strategy, card sort strategy, subject of akidah akhlaq.